Ecological influence by colonization of fluoride-resistant Streptococcus mutans in oral biofilm - Shen, Yan; Yu, Fangzheng; Qiu, Lili; Gao, Mengjia; Xu, Puxin; Zhang, Lingjun; Liao, Xiangyan; Wang, Min; Hu, Xiangyu; Sun, Yan; Pan, Yihuai (Frontiers in Cellular and Infection Microbiology, 2023)
Dental caries is one of the oldest and most common infections in humans. Improved oral hygiene practices and the presence of fluoride in dentifrices and mouth rinses have greatly reduced the prevalence of dental caries. However, increased fluoride resistance in microbial communities is concerning. Here, we studied the effect of fluoride-resistant Streptococcus mutans on oral microbial ecology and compare it with wild-type S. mutans in vitro. Biofilm was evaluated for its polysaccharide content, scanning electron microscopy (SEM) imaging, acid-producing ability, and related lactic dehydrogenase (LDH), arginine deiminase (ADS), and urease enzymatic activity determination. Fluorescence in situ hybridization (FISH) and quantitative real-time polymerase chain reaction (qRT-PCR) were used to evaluate the S. mutans ratio within the biofilm. It was followed by 16S rRNA sequencing to define the oral microbial community. Fluoride-resistant S. mutans produced increased polysaccharides in presence of NaF (P < 0.05). The enzymatic activities related to both acid and base generation were less affected by the fluoride. In presence of 275 ppm NaF, the pH in the fluoride-resistant strain sample was lower than the wild type. We observed that with the biofilm development and accumulative fluoride concentration, the fluoride-resistant strain had positive relationships with other bacteria within the oral microbial community, which enhanced its colonization and survival. Compared to the wild type, fluoride-resistant strain significantly increased the diversity and difference of oral microbial community at the initial stage of biofilm formation (4 and 24 h) and at a low fluoride environment (0 and 275 ppm NaF) (P < 0.05). Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis revealed that fluoride-resistant strain enhanced the metabolic pathways and glucose transfer. In conclusion, fluoride-resistant S. mutans affected the microecological balance of oral biofilm and its cariogenic properties in vitro, indicating its negative impact on fluoride's caries prevention effect.